ANALYSIS OF EINAR’S NEEDS IN THE DANISH GIRL FILM USING MASLOW’S THEORY - Katedral Velty Nila; M. Natsir; Setya Ariani (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2022)
The research discusses the main character’s needs in a movie titled The Danish Girl. The Danish Girl tells the story of Einar Wegener, a painter who decided to be transgender after he became a woman model for the painting of his wife, Gerda. He became two different people incorporated in a body. First, he was a talented painter and a great husband. Second, he was Lili Elbe, an elegant woman who was the model of Gerda’s painting. The research aims to find out how Einar met his needs in life using Maslow’s Hierarchy of Needs theory. The research applies a qualitative research method and the findings are presented in descriptively. The research finds that Einer Wegener managed to meet his needs for physiological needs, security, love and belonging, and esteem. The findings reveal that Einar Wegener failed to meet the self-actualization need. The researcher finds that Einar Wegener wanted to complete his transformation to be a woman to secure a happier and more comfortable life. When Einar transformed into Lili following, Einar no longer painted and buried Einar’s biggest talent as a painter. He merely focused to make a total transformation to be Lili following his decision for surgery. At last, he passed away before fulfilling his need to be a real woman. Therefore, it can be concluded Einer failed to meet his self-actualization need.